2013
DOI: 10.24926/iip.v4i1.288
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacists' Awareness of Intimate Partner Violence: An Exploratory Study

Abstract: Acknowledgements:The authors would like to thank all of the pharmacists who responded to the survey. Conclusions: Most respondents indicated relatively low levels of IPV knowledge and training and very little current IPV screening activity. Continuing education on IPV should be considered for pharmacists to increase knowledge and awareness of IPV. IntroductionIntimate partner violence (IPV), also known as domestic violence, is a public health problem impacting more than 12 million people in the United States … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…18 While our survey indicated that student pharmacists recognized their team members as resources in assisting victims of domestic violence, the literature supports a greater need for pharmacist/ student training in screening for and recognition of intimate partner violence. 19 …”
Section: Discussionmentioning
confidence: 99%
“…18 While our survey indicated that student pharmacists recognized their team members as resources in assisting victims of domestic violence, the literature supports a greater need for pharmacist/ student training in screening for and recognition of intimate partner violence. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Research relating to IPV training for pharmacists has shown their lack of awareness, readiness, and knowledge among pharmacists on how to respond to suspected cases of IPV. In a cross-sectional study with 144 community pharmacists, 67.4% of participants reported no IPV-related training at all 40. A majority of those surveyed (77.6%) were also uncertain if there was a legal mandate in their state of practice to report suspected cases of IPV 40.…”
Section: Role Of Pharmacistsmentioning
confidence: 99%
“…Two of the most frequently reported barriers to the provision of quality IPV-related care in other health care provider groups are a general lack of training and a lack of awareness of appropriate methods for referrals [ 24 , 25 , 26 , 27 ]. Three studies have examined IPV knowledge and awareness in community pharmacists and found that pharmacists also report that they lack knowledge and preparation related to IPV, despite the fact that most report they have encountered victims in practice [ 23 , 28 , 29 , 30 ]. In order to provide the highest quality patient-centered care, educational interventions are needed for pharmacists.…”
Section: Introductionmentioning
confidence: 99%